Assessing Employee Performance Based on Work Motivation and Work Ability - Wiranti, Wiranti; Zainarti, Zainarti; Atika, Atika (Image : Jurnal Riset Manajemen, 2023)
This study aims to investigate how employee performance at PT. North Sumatra Plantation Simpang Gambir, Mandailing Natal, is affected by work motivation and work ability At PT. North Sumatra Plantation Simpang Gambir, Mandailing Natal. In this study, the author uses both a quantitative and an associative technique. A total of 212 employees of PT. North Sumatra Plantation Simpang Gambir, Mandailing Natal, make up the study's population. Out of this population, 68 employees make up the study's sample. The result show, work motivation has a strong partial impact on performance. Work ability has also strong partial impact on employee performance at PT. North Sumatra Plantation Simpang Gambir, Mandailing Natal, This suggests that the combined impact of work motivation and work ability on performance is substantial. The important implication of the results of this study shows that increasing employee work motivation and work ability at PT. Perkebunan Sumatera Utara Simpang Gambir, Mandailing Natal, will significantly improve employee performance. Therefore, companies should focus on developing training programs and providing appropriate incentives to maximize employee potential